Silas Marner - Eliot, George, 1819-1880 (Friends Classics, 2006)
In rural nineteenth-century England, a weaver, lonely and embittered at the unjust treatment he has received from people he considered to be his friends, finds his only solace in money until he inadvertently becomes the guardian of an orphaned little girl. Includes explanatory notes throughout the text, an introduction discussing the author and the background of the story, and a study guide.